Identifying and addressing gaps in the UNFCCC reporting framework - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2015)
There are many reasons why the United Nations Framework Convention on Climate Change (UNFCCC) reporting framework requests information from countries. These include understanding and tracking progress with individual or collective commitments or pledges, providing confidence and enhancing accountability in quantified information measured and reported, and providing background information on the scope and ambition of national climate responses. This paper highlights the gaps, inconsistencies and uncertainties in the current reporting framework, which was developed for both long-standing obligations and mitigation pledges for the period to 2020. The paper also identifies possible improvements in the UNFCCC reporting framework in the context of the post-2020 transparency framework and nationally determined contributions (NDCs) for the post-2020 period